Orientations of government public relations practice in Malaysia: a pre-independence and post-colonialism perspectives - Selamat, Muhamad Rosli; Rosli, Muhamad Ridhwan (South Shields Center, 2015)
This article, conceptually explores the orientation of the practice of public relations in Malaysia (formerly known as Malaya) during the last decade of British occupation and the first decade of post independence based on historical perspective. The post colonialism of British administration addressed the significance influence of British strategic approach of public relations practice in the newly independence nation. Being a Malay state/country and gaining independence through negotiation and not war, the influence of postcolonialism is clearly acknowledged through the appointment of a local British and English educated Director Generals for the Department of Information, functioning as the head of the government public relations officer. Nonetheless, independence meant that the newly independent nation has every right to forgo the colonialism influence, but the case of Malaya is extremely different. Being the majority, the Malay administrators maintained their culture of loyalty by respecting and tolerating their former superior British administrators “post-colonialism” by assimilating and adopting their public relations strategic practices throughout the first decade of post independence Malaya.